Representações sociais sobre terapia comunitária integrativa construídas por idosos e profissionais de saúde - Moura, Samilla Gonçalves de (2015)
The present study is of exploratory type based on structural contribution of the Theory of Social Representations. It aimed to knowing the structure of social representations of the elderly and health professionals about the Integrative Community Therapy and to compare. It involved 263 elderly and 247 professionals of service network of SUS in João Pessoa-Paraiba. Data were collected through the Word Free Association Test (TALP) by the term inducer community therapy and treated through the EVOC software. It is understood that the elderly and the professionals give to TCI the meaning of a gathering of people who develop group activities to ensuring through communication the outburst of their problems and getting help for their resolution and restoration of joy in life. Reporting to the peripheral system, we can see that the elderly reinforce the sense of TCI as an experience exchange space and outburst of what brings you concern, promoting health. For them, in TCI, the professionals, in the case, the therapists, develop wheels using art resources to build distraction moments and provide a deep introspective journey to awakening the Self and the love of self and other. Professionals represent the problem as sadness generator and suffering, and a challenge to be faced, requiring for it, mind and knowledge of intrinsic and collective capacities to solving these. To do so, attach the TCI the meaning of important care tool facilitated by professionals, in this case the community therapists; who, through group activity, creates a therapeutic and treatment space, promoting improvement of the physical or mental condition by awakening to love of self and other. Thus, resulted that the cohesive and well-structured representation of the peripheral and central elements of the RS of the elderly and the professionals, reflected the presence of elements that assert the acceptance of ICT as a practice of community mental health. Despite the higher level of education and socio-occupational status, representation the professionals did not differ much from that expressed by the elderly, who had a lower social and educational background. The striking resemblance, but not absolute identity between the central cores shows that the common elements evoked by the two groups, should not therefore have its origin in formal education or in specialized occupational practices. It is probably of representational elements of deeper entrainment and more constant confirmation in the daily life of the subjects. As for what distinguishes the core of RS the professional only compressed the matter retained in the representation of the elderly; in turn, the peripheral system expanded. In this sense, there is a "popular theory" of what the TCI, understood from the idealization of an academic scholarship to the branch of knowledge artistic. Finally, knowing the RS of TCI is a strengthening of conduct of this care tool.